Conserved Sequence Processing in Primate Frontal Cortex. Issue 2 (February 2017) - Wilson, Benjamin; Marslen-Wilson, William D.; Petkov, Christopher I.
Abstract : An important aspect of animal perception and cognition is learning to recognize relationships between environmental events that predict others in time, a form of relational knowledge that can be assessed using sequence-learning paradigms. Humans are exquisitely sensitive to sequencing relationships, and their combinatorial capacities, most saliently in the domain of language, are unparalleled. Recent comparative research in human and nonhuman primates has obtained behavioral and neuroimaging evidence for evolutionarily conserved substrates involved in sequence processing. The findings carry implications for the origins of domain-general capacities underlying core language functions in humans. Here, we synthesize this research into a 'ventrodorsal gradient' model, where frontal cortex engagement along this axis depends on sequencing complexity, mapping onto the sequencing capacities of different species. Trends: Cross-species studies of sequence processing are providing insights into combinatorial learning in nonhuman animals that may represent evolutionary precursors to human language-related operations. Recent comparative neuroimaging studies in humans and monkeys provide neurobiological evidence for evolutionarily conserved sequencing processes, supported by functionally homologous subregions of frontal cortex in humans and monkeys. These findings point to further development of animal model systems in which the neuronal mechanisms that support these operations can be studied in ways not feasible in humans. A heuristic 'ventrodorsal gradient' model is proposed of primate frontal cortex engagement that depends on sequencing complexity.